Analisis Penerima Bantuan Beasiswa Program Studi Teknik Informatika Menggunakan Metode MOORA dan TOPSIS - Yunita Sari Siregar (JITEKH, 2021)
During the current pandemic, there are many permanent or temporary termination of employment by the company so that it has a very significant impact on the income of parents or students, where the reduced income generated makes it difficult for students to pay tuition fees every year. Therefore, in this study, a comparative analysis of the feasibility of students to be able to receive scholarship assistance will be carried out using the Moora and Topsis methods. Moora method is one of the methods in a decision support system where the way it works is by creating a normalization matrix and calculating the optimization value of each attribute, resulting in a ranking that is done by reducing the maximum and minimum values. While Topsis method is a method that produces rankings by making alternative preferences and comparing the results of the best alternatives. The variables used in the simulation of the eligibility analysis of scholarship recipients are the Grade Point Average (GPA), Parents' Income, House Type and Children's Dependents. The results of the research using the Moora method get an accuracy value of 70% , while the Topsis method gets an accuracy value of 80%. So it can be said that the Moora method produces better decisions in the selection of eligibility for scholarship recipients in the Informatics Study Program